t the feet of the goddess. Context and analysis of the Greek marble sculpture documented in the courtyard of the tartessic site of Casas del Turuñuelo (Guareña, Badajoz, Spain) - Celestino Pérez , Sebastián; Rodríguez González , Esther; Gutiérrez García , Ana; Dorado Alejos , Alberto (Complutum, 2023)
In this paper we present the results of the archaeometric analyzes carried out on a fragment of marble sculpture documented in the courtyard of the Casas del Turuñuelo site (Guareña, Badajoz) during the 2017 works. These analyses have confirmed that the marble comes from the Pentelic quarries (Athens, Greece), which makes it the oldest Greek marble sculpture, to date, of peninsular archaeology. His study has also made it possible to recover the remains of polychromy and to characterize the pigments used. Finally, the archaeological and historical context of the piece under study is presented, as well as its possible parallels.